Phenotypic Characterization of Indigenous Frizzle Feathered Chicken in Nepal - Poudel, Dikshya; Bhattarai, Nirajan; Bashyal, Soniya (International Journal of Livestock Research, 2021)
Phenotypic characterization of chicken is important for differentiating them among the breed and to understand the role of these phenotypic traits on body performance. Phenotypic traits like body plumage color, morphology of feathers, shank size, shank color, ear lobe and eye color, different comb and their size etc. are noted for characterization of indigenous chickens phenotypically. The indigenous chicken breed i.e., Sakini, Ghati khuile, Pwankh ulte of Nepal, which also have a major role in back yard poultry can be differentiated based on phenotypic characters. Indigenous frizzle feather differs from the other two having typical curled (frizzled) plumage. The skin color varies from yellow to pink, shank color yellow, red earlobe, eye color varies among males and females of these breeds and they have a single rose comb with comb color usually red /pink. These chickens are on the verge of extinction and need urgent works related to their conservation.